THE BINARY CHARACTER OF THE CATEGORY "WONDER" (Spectrum Journal of Innovation, Reforms and Development, 2023)
In this article, the essence and binary nature of the category of "surprise" are studied on the example of Alisher Navoi's works "Lison ut-tayr" and "Hayrat ul-abror".